Study of nurses 'collaboration in managing decision making - Rostamniya, Leili; Ghanbari, Vahid; Paryad, Ezzat; Momeni, Maryam; Khoshnazar, Tahereh sadat; Khazaee, Nahid (Advances in Nursing & Midwifery, 2013)
Abstract: Background and aim: Nowadays collaboration of stuffs in decision making has accepted to improve the strength and efficacy of each organization. Nurses are the biggest care delivering group and their collaboration in decision making in managing domains, can improve the quality of care. The aim of this study was to determine the nurses’ decision making collaboration in managing domains. Materials and Methods: This cross sectional study was done in educational medical centers of Guilan University of medical sciences in Rasht from august to September of 2010.by stratified randomized sampling 193 questionnaire was given to nurses and only 99 of them were filled. The tool of study was demographic and PDA Questionnaire (Participation in Decision making Activities). Data analyzing was done by descriptive and inferential statistics such as Pearson, T test and ANOVA. Findings: The findings showed the score of nurse collaboration were higher than mean score and the relationship between shift and claryfing the problem domain (p<0.02) and generating and evaluating domain ( p<0.04) were significant. Pearson test showed the relationship between age and clarifying the problem was significant (p<0.04). Other demographic data didn't have significant relationship with mean score of collaboration. Conclusion: The score of nurses ' collaboration in this study was higher than mean score of tool, but this difference wasn't remarkable. Nurses have the highest participation in caring and it seems improving of their collaboration in managing domain, would have useful results. Keywords : Decision making ,Cooperative behavior, Nursing stuff